2018
DOI: 10.1024/1422-4917/a000589
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data of the Self-Report Version of the German Strengths and Difficulties Questionnaire in an Epidemiological Setting

Abstract: This study of the German SDQ-S in a large representative epidemiological sample presents evidence of partly moderate to good psychometric properties. It also supports the usefulness of SDQ-S as an effective and efficient instrument for child and adolescent mental health problems in Germany. German normative banding scores of SDQ-S established in this study were comparable with the original British norms as well as with those of other countries, so that SDQ-S can be recommended as a psychopathological broadband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
52
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 53 publications
13
52
0
5
Order By: Relevance
“…The internal consistency (indicated by Cronbach’s alpha) was 0.65 in the sample of younger children and 0.69 in the sample of older children, which is comparable with the internal consistencies observed in German normative samples (0.66 [ 44 ] and 0.62 [ 45 ], respectively). Based on the German reference values, the score was dichotomized into “low/normal” (scores 0–3 in the sample of younger children [ 44 ] and scores 0–4 in the sample of older children [ 45 ]) and “borderline/abnormal” (all scores above 3 or 4, respectively). The cut-off values were chosen so that 15% of the children/adolescents were assigned to the “borderline/abnormal” group [ 44 , 45 ].…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The internal consistency (indicated by Cronbach’s alpha) was 0.65 in the sample of younger children and 0.69 in the sample of older children, which is comparable with the internal consistencies observed in German normative samples (0.66 [ 44 ] and 0.62 [ 45 ], respectively). Based on the German reference values, the score was dichotomized into “low/normal” (scores 0–3 in the sample of younger children [ 44 ] and scores 0–4 in the sample of older children [ 45 ]) and “borderline/abnormal” (all scores above 3 or 4, respectively). The cut-off values were chosen so that 15% of the children/adolescents were assigned to the “borderline/abnormal” group [ 44 , 45 ].…”
Section: Methodssupporting
confidence: 74%
“…Based on the German reference values, the score was dichotomized into “low/normal” (scores 0–3 in the sample of younger children [ 44 ] and scores 0–4 in the sample of older children [ 45 ]) and “borderline/abnormal” (all scores above 3 or 4, respectively). The cut-off values were chosen so that 15% of the children/adolescents were assigned to the “borderline/abnormal” group [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…For some of the assessed aspects of mental/physical health, instances of the child reporting more problems/symptoms than their parent were more common with female children than with male children. Several previous studies have shown that girls report more mental health problems than boys [56][57][58]. The present finding suggests that this gender effect is weaker if indicators of the child's mental health are estimated by a parent.…”
Section: Plos Onesupporting
confidence: 40%
“…Thornberry & Krohn [34] found that generally adolescents answer such questions truthfully and concluded that selfreport data on problem behavior "appear acceptably valid and reliable for most research purposes" (p. 33). Additionally, recent research has shown evidence for the predictive power of children's self-reports [35]. Thus, since self-reports could provide an interesting new perspective on heritability of INT and EXT and as there is evidence for their validity, we base our current study on self-reported INT and EXT.…”
Section: Introductionmentioning
confidence: 99%